2021
DOI: 10.1149/1945-7111/abe088
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Products Electrochemical Behaviour into Molten LiF-NaF: Investigation of Cr(II) System

Abstract: In this work, a detailed electrochemical study of the molten LiF-NaF-CrF2 system is provided on Ag electrode in the 750 °C–900 °C temperature range. The first part was dedicated to the electrochemical study, by cyclic and square wave voltammetries, allowing the determination of thermodynamic and physico-chemical data such as CrF2/Cr standard potential, diffusion coefficient, activity coefficient, transfer energy and nucleation overvoltage. The influence of Li2O addition on the electrochemical reduction pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Prior to each experiment, a CV analysis was performed on a Pt electrode to identify possible impurities that can act as redox couples. 4,17,18,73 Apparatus.-Figure 1 shows the electrochemical cell developed to carry out electrochemical tests in molten salts. The experiment was performed in a N 2 -filled glove box.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to each experiment, a CV analysis was performed on a Pt electrode to identify possible impurities that can act as redox couples. 4,17,18,73 Apparatus.-Figure 1 shows the electrochemical cell developed to carry out electrochemical tests in molten salts. The experiment was performed in a N 2 -filled glove box.…”
Section: Methodsmentioning
confidence: 99%
“…These values support not only the thermodynamic phase stability maps (based on the n transferred for corrosion in each regime) but also imply that the total anodic reaction may involve some combination of half-cell reactions 10 and 12. While the literature has demonstrated that Cr(III) is more prevalent in molten fluorides, electrochemical studies of FLiNaK salts containing CrF 2 or CrF 3 species on a Pt wire have shown that 88-92% of Cr(II) can be oxidized to Cr(III) 16,17,29,[42][43][44][45] when a sufficient driving force is present, either controlled by applied potential or varying the concentration of oxidizers.…”
Section: Hf Ms E H G F Ms 13mentioning
confidence: 99%
“…25 A DRE produced with CV has been used to measure the voltammetric behavior of dissolved CrF 2 with respect to the Na/Na + redox couple in LiF-NaF. 28 In the authors' previous work, 26 a Be/Be 2+ DRE was created using a linear sweep voltammogram to form the Be/Be 2+ electrode. Its potential was determined with a subsequent open circuit potential (OCP) measurement.…”
Section: State Of the Art Fluoride Salt Reference Electrode Methodsmentioning
confidence: 99%
“…Furthermore, electrochemical techniques have been widely used in the study of molten salt corrosion, [ 16–22 ] and have been proved to be effective in understanding corrosion mechanisms, kinetics, and corrosion process. Fernández et al [ 23 ] investigated the positive effect of alumina‐forming on corrosion behavior of austenitic stainless steel using EIS method in molten nitrate salts.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from this, the evaluation of the corrosion behavior of SS in molten nitrate salts containing high-content chloride impurity is limited. There are few investigations on the corrosion behavior of austenitic SS in molten nitrate salts containing chloride higher than 1 wt% by electrochemical measurements, especially electrochemical impedance spectroscopy (EIS), which is regarded as the effective and reliable technique for corrosion monitoring in CSP plants according to Encinas-Sánchez et al [16] Furthermore, electrochemical techniques have been widely used in the study of molten salt corrosion, [16][17][18][19][20][21][22] and have been proved to be effective in understanding corrosion mechanisms, kinetics, and corrosion process. Fernández et al [23] investigated the positive effect of alumina-forming on corrosion behavior of austenitic stainless steel using EIS method in molten nitrate salts.…”
mentioning
confidence: 99%